2012
DOI: 10.1155/2012/919128
|View full text |Cite
|
Sign up to set email alerts
|

Renal Development and Blood Pressure in Offspring from Dams Submitted to High-Sodium Intake during Pregnancy and Lactation

Abstract: Exposure to an adverse environment in utero appears to programme physiology and metabolism permanently, with long-term consequences for health of the fetus or offspring. It was observed that the offspring from dams submitted to high-sodium intake during pregnancy present disturbances in renal development and in blood pressure. These alterations were associated with lower plasma levels of angiotensin II (AII) and changes in renal AII receptor I (AT1) and mitogen-activated protein kinase (MAPK) expressions durin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 37 publications
0
10
0
3
Order By: Relevance
“…High-salt intake during pregnancy outcome of kidney functions of offspring after renal I/R gender dependently. The offspring from mothers received salt diet during pregnancy performs a higher blood pressure (3,7), and the RAS in offspring also influences by salt intake during pregnancy (12,13). It also is reported that salt diet during pregnancy alters the kidney structures of offspring (4,7,14), and therefore this alteration may affect the adult offspring's kidney function.…”
Section: Male Femalementioning
confidence: 99%
See 1 more Smart Citation
“…High-salt intake during pregnancy outcome of kidney functions of offspring after renal I/R gender dependently. The offspring from mothers received salt diet during pregnancy performs a higher blood pressure (3,7), and the RAS in offspring also influences by salt intake during pregnancy (12,13). It also is reported that salt diet during pregnancy alters the kidney structures of offspring (4,7,14), and therefore this alteration may affect the adult offspring's kidney function.…”
Section: Male Femalementioning
confidence: 99%
“…High salt diet during pregnancy may alter some physiological functions and organs developments (1)(2)(3)(4)(5). Milk content may also change with high salt diet (6), and the offspring from mothers that received high salt diet during pregnancy demonstrated a higher blood pressure (3,7). It is well-known that renin secrets by glomerular cells which are salt sensitive and high salt diet disturb renin secretion in offspring and may develop hypertension (8).…”
Section: Introductionmentioning
confidence: 99%
“…Outros estudos demonstraram que a restrição de sódio pode aumentar os níveis de peptídeo -C e insulina sem alteração no nível da glicose sérica, o que sugere uma resistência à insulina na captação periférica de glicose (Lind et al,1992;Fliser et al, 1993. Prada et al, (2000 (Coimbra et al, 2012;Eriksson et al, 2007;Ding et al, 2010).…”
Section: Discussionunclassified
“…Embora essas alterações possam ser decorrentes de ambiente adverso durante períodos críticos de desenvolvimento podendo envolver fatores de crescimento e alterações da atividade do SRA que tem um papel importante na nefrogênese (Coimbra et al, 2012), tais como os seus componentes expressos na fase metanefro no rim embrionário, conforme mostra a tabela1, podendo comprometer o número de néfrons (Bagby et al, 2007;Woods et al, 2004).…”
Section: Koleganova E Seus Colaboradores (2011) Investigaram As Conseunclassified
See 1 more Smart Citation